Augmented Shared Spaces: An Application for Exposure Psychotherapy - Patrão, Bruno; Menezes, Paulo; Gonçalves, Nuno (International Journal of Online and Biomedical Engineering (iJOE), 2020)
The latest advances in computational power of small portable devices enables the development of new forms of Augmented Realities, namely Augmented Reality Shared Spaces. In this work, we will explore this technolo- gy to improve the collaborative work between people in the same physical space allowing them to share and visualise virtual contents. The idea is to have a 3D scene shared between several people where everyone can see and interact with and explore its use in psychotherapy context. These live interactions can also be used to improve the quality of collaborative work by presenting in real time ideas and thoughts of any participant directly on top of the 3D model. In the case of a psychotherapy session typically patients describe their feelings and fears to the therapist. This may be centred on virtual representations of their phobic elements, supporting interactions with them, being those actions and re- sults observable by both in their shared space. Our main goal is to apply and evaluate this concept, specially in exposure-based therapies, where it is im- portant for the therapist to control and manipulate the scene that the patient is exposed to in order to obtain the desired emotional activations.